Ancillary academia: video shorts and the production of university paratexts - Grainge, Paul (Routledge, 2017)
This article considers the production of media paratexts beyond the bounds of the entertainment industry. Specifically, it examines the development of video content strategy by universities, and the paratextual function that video shorts serve in the construction of institutional identity. Taking a production studies approach, the article expands the scope of paratextual analysis by exploring the development of video content by university marketers, and the role of promotional intermediaries in selling video expertise to the education market.